EDUKASI KODE KEMASAN DAN KEMASAN RAMAH LINGKUNGAN PADA UMKM JAJAN BIE PALEMBANG - Erlinawati; Ira Gusti Riani; Raudhatus Saadah (Politeknik Negeri Sriwijaya, 2024)
Bie's snack packaging currently still uses plastic and Stryofoam. This packaging is still commonly used by household, micro and medium entrepreneurs because it is cheaper, practical and easy to find. However, this type of packaging is not environmentally friendly. This service aims to educate about plastic packaging codes and environmentally friendly packaging for Palembang Bie Snack. This activity began with a location survey and discussion with the owners of Palembang Bie Snack regarding the problems faced in entrepreneurship. This activity was carried out offline by providing knowledge and information regarding packaging codes, types of packaging, dangers of packaging and packaging that is environmentally friendly and safe for food. It is hoped that after this training the community will have the ability to process coconut water into nata de coco.